Breeding for enhanced ß-Carotene content in cassava: constraints and accomplishments - Njoku, DN; Vernon, G; Egesi, Chiedozie N.; Asante, I.K.; Offei, SK; Okogbenin, Emmanuel; Kulakow, Peter A.; Eke-Okoro, O.N.; Ceballos, H. (Informa UK Limited, 2011)
This review presents an overview of the importance, constraints, and prospects on different aspects of cassava (Manihot esculenta crantz) breeding for enhanced micronutrient level, including carotenoids (precursors for provitamin-A) and especially beta-carotene. Early cassava-breeding efforts concentrated on crop yield, dry matter, and disease resistance, which are farmer-preferred traits. However, unacceptably high levels of preventable human diseases caused by malnutrition prompted breeders and nutritionists to screen wild relatives and unimproved germplasms (landraces) to increase micronutrient density in staple crops. The ultimate objective is to reduce diseases caused by micronutrient deficiencies. Nigeria, with 140 million people and the largest producer and consumer of cassava in the world, is characterized by rampant malnutrition and high incidence of nutrient deficiency-related diseases. The tuberous root of cassava is low in micronutrients. It is also well known that vitamin A deficiency is primarily caused by dietary inadequacy that results in progressive eye damage and eventually leads to blindness, especially in children. In addition, affected children suffer from a weakened immune system. Present interventions to eliminate this deficiency rely on supplementation and food fortification programs, do not reach all those affected and do not get to the root of the problem, which is an inadequate diet. The development of high micronutrient-content cassava varieties (especially, higher ?-carotene and other carotenoids) will contribute to a more sustainable solution of the problem of vitamin A deficiency. A current thrust of research (HarvestPlus initiative) is to determine the genetic potential for increasing the concentrations of bioavailable Fe, Zn, and provitamin A carotenoids in the edible portions of several staple food crops including cassava, rice, wheat, maize, and beans. Currently, the International Institute of Tropical Agriculture (IITA), International Center for Tropical Agriculture (CIAT), and National Root Crops Research Institute (NRCRI), Umudike, are working in collaboration to develop an elite cassava gene pool and to develop varieties that will be released to farmers soon in hope of addressing part of micronutrient malnutrition.